The socializing function of the university - Seregina Tatiana N.; Prosekov Sergey A.; Nazarenko Sergey V.; Logunov Maxim R. (SHS Web of Conferences, 2021)
The article considers the role of the university as a social institution in the urban space. The article establishes the connection and interdependence among the phenomena of the city, the university, the type of rationality, and the type of communication. The transformations of urban space and the functions of the city in history affect the organizational forms and functions of the university. The research environment at the university, using the communication practices that have developed in society, creates a certain type of rationality. The nonclassical type of rationality is formed in the industrial city environment, and university education is changing towards professionalization, and commercialization, changing communication practices and values that need to be mastered for socialization into the industrial world. The post-nonclassical type of rationality coincides with the emergence of a new type of university, created within the framework of the Bologna Process. This is associated with the emergence of so-called multiple identities, formed by a variety of socialization practices. Universities are operating in the global space of global cities and megalopolises. The convergence of these phenomena results in the transformation of the value perception of the world and the axiological paradigm of society. The activity-based method of analyzing the socialization process allowed determining the need to create the idea of a university, based on a value approach. Values and value-based communication practices in the educational system of the university allow moving to a sustainable development society.